Argentine command structure and its impact on land operations during the Falklands/Malvinas War (1982) - Alejandro L. Corbacho (Universidad del Centro de Estudios Macroeconómicos de Argentina (UCEMA), 2006)
This paper claims that besides training and equipment shortcomings, Argentine command structure was another source of problems that affected the military operations during the Falklands/Malvinas Campaign during April-June 1982. Consequently, the flawed command structure can be seen as a contributing factor in Argentina's military defeat. Improvisation, confusion, lack of coordination, and desperation prevailed along the command structure throughout the conflict. Operational and tactical commands were seem to be pulling apart between the political imperatives of the High Command in Buenos Aires that transcended to the islands and the military imperatives of the front. This handicap was critical to conduct operations. By using official documents, reports and accounts and the own participants' testimonies, this paper clarifies the issues connected with the structure of the Argentine High Command and it furthers our understanding of how the Argentine armed forces functioned.
Keywords: 330